Unmet needs in the treatment of idiopathic pulmonary fibrosis―insights from patient chart review in five European countries - Maher, Toby M. (BMC Pulm Med, 2017)
BACKGROUND: Two antifibrotic drugs, pirfenidone and nintedanib, are approved by the European Medicines Agency and the US Food and Drug Administration for the treatment of idiopathic pulmonary fibrosis (IPF). In this analysis, treatment patterns of European patients with IPF were investigated to understand antifibrotic prescribing and identify unmet needs in IPF treatment practice. METHODS: Between February and March 2016, respiratory physicians from France, Germany, Italy, Spain, and the UK participated in an online questionnaire designed to collect information on IPF treatment patterns in patients under their care. Patients were categorized as treated (received approved antifibrotics) or untreated (did not receive approved antifibrotics, but may have received other unapproved therapies). Classification of IPF diagnosis (confirmed/suspected) and severity (‘mild’/‘moderate’/‘severe’) for each patient was based on the individual physician’s report. Patients’ perspectives were not recorded in this study. RESULTS: In total, 290 physicians responded to the questionnaire. Overall, 54% of patients with IPF did not receive treatment with an approved antifibrotic. More patients had a confirmed IPF diagnosis in the treated (84%) versus the untreated (51%) population. Of patients with a confirmed diagnosis, 40% did not receive treatment. The treated population was younger than the untreated population (67 vs 70 years, respectively; p ≤ 0.01), with more frequent multidisciplinary team evaluation (83% vs 57%, respectively; p ≤ 0.01). A higher proportion of untreated patients had forced vital capacity > 80% at diagnosis versus treated patients. Of patients with ‘mild’ IPF, 71% did not receive an approved antifibrotic versus 41% and 60% of patients with ‘moderate’ and ‘severe’ IPF, respectively. CONCLUSIONS: Despite the availability of antifibrotic therapies, many European patients with confirmed IPF do not receive approved antifibrotic treatment. Importantly, there appears to be a reluctance to treat patients with ‘mild’ or ‘stable’ disease, and instead adopt a ‘watch and wait’ approach. More education is required to address diagnostic uncertainty, poor understanding of IPF and its treatments, and issues of treatment access. There is a need to increase physician awareness of the benefits associated with antifibrotic treatment across the spectrum of IPF severity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12890-017-0468-5) contains supplementary material, which is available to authorized users.